Investigation on electric motor as an actuator of anti skid control system to improve the safety of small electric vehicle - Mohamad Heerwan, Peeie; Mod Razali, Hanipah; Ahmad Fitri, Yusop; Saiful Anwar, Che Ghani; Priyandoko, Gigih; Mustafizurahman, Md; Rizalman, Mamat; Syafiq Fauzi, Kamarulzaman (2018)
Small electric vehicle (EVs) only employed seat belt and a mechanical brake system as a safety system. Without ABS and hydraulic braking system, the tire can be locked up and the possibility of an accident is increased. The main objective of this research is to improve the safety by using the electric motor as an actuator of anti-skid control system. During braking, if the slip ratio greater than the optimum value, the motor controller will send the signal to the motor to turning forward, and if the slip ratio becomes smaller than the optimum value, the motor will be running backwards. In this research, the simulation will be developed in MATLAB/Simulink, and the experiment will be conducted on the small EV.